Mile high on heroin: Lessons on the opioid epidemic from the Mile High City. (31st March 2022) - Peters, Jamie
Abstract : This commentary discusses the novelty of the preclinical opioid choice model published in Heinsbroek et al., Nat Commun, 2021, and the potential influence of altitude on the reported findings. The studies were performed in the Mile High City of Denver, Colorado, where a unique subpopulation of heroin‐choosing rats were noted.